Usulan Perbaikan Kerja Kuli Panggul Beras Menggunakan Cocorometer dan Subjective Self Rating Scale (SSRT) Serta Hubungan Parameter Stres dan Kelelahan Pada Perusahaan X Di Kota Bandung - Asterina Febrianti; Annisa Nurul Khotimah (Jurnal Rekayasa Sistem Industri, 2020)
It was noted that from 2011 to 2017 rice production in Indonesia had increased by 23.77%. Perusahaan X is a rice supplier company in Bandung city with the transfer of rice carried out by porters (kuli panggul) manually without tools. Porters do the lifting process with a duration of 9 hours and the load carried weights from 10 kg to 50 kg. Repetitive and monotonous task can increase stress levels and fatigue at work. Improvement  of work condition is needed through the measurement of stress and fatigue level on the porters of rice in Perusahaan X using cocorometer and The Subjective Self Rating Test (SSRT) questionnaire to increase productivity in the company. Ten men as respondent with ages ranging from 20-41 years with work experience of 1-6 years were tested. The result shows that respondents before work (α/2table< α/2calculated< α/2tableor 0.025 < 0.544 < 0.975) and after work (α/2table< α/2calculated< α/2tableor 0.025 < 0.413 < 0.975) experienced increased stress and fatigue level. The correlation between stress and fatigue level before work (degree of freedom = -0.219) and after work (degree of freedom = -0.292) shows low correlation. Stress level is not only influenced by fatigue level but also influenced by the age and work experience of respondents during work. Perusaahaan X should do several things to reduce the increased in stress and fatigue by creating a pleasant atmosphere at work; requiring the workers to do stretching at rest break; providing  bonus; and providing drinking water so that respondents are not dehydrated. Keywords: Stress, fatigue, cocorometer, SSRT